2021
DOI: 10.1111/ijcp.14685
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatitis B screening and reactivation in patients receiving rituximab containing chemotherapy: A single‐centre study

Abstract: Hepatitis B virus (HBV) infection is a worldwide distributing viral disease. It is estimated that over than 250 million people are chronically infected with HBV. 1 Hepatitis B core antibody (AntiHBc) prevalence is considered to be higher particularly in endemic countries. 2 Because of that reason HBV reactivation may be common in endemic areas among patients who require immunosuppressant therapy. In the settings of Hepatitis B surface antigen (HBsAg) clearance from circulation. viral genome continues to exists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…However, multivariate analysis demonstrated that ethnicity was not associated with screening performance. Finally, our findings might only be generalizable to other low-endemic countries, although similar HBV screening rates were reported in both low-and higher-risk areas as well [16,18,21].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, multivariate analysis demonstrated that ethnicity was not associated with screening performance. Finally, our findings might only be generalizable to other low-endemic countries, although similar HBV screening rates were reported in both low-and higher-risk areas as well [16,18,21].…”
Section: Discussionsupporting
confidence: 69%
“…Nevertheless, findings from several studies suggest that screening might be performed sub optimally (Supplementary Table) [16][17][18][19][20][21]. In the Netherlands, a low endemic country, data on the screening rates among patients treated with high risk immunosuppressive agents are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 29 studies, six conference abstracts 26,[29][30][31]35,43 with sufficient information on HBV screening counts were also included. The studies reported hematologic malignancy (10 studies), [27][28][29][30]34,41,43,45,48,54 solid malignancy (four studies), 31,44,47,50 or a combination of both (15 studies). 26,32,33,[35][36][37][38][39][40]42,46,49,[51][52][53] The studies also included rituximab-containing (seven studies), 27,28,30,34,41,43,54 non-rituximab (four studies), 31,42,44,46 or both regimens (seven studies), 32,33,36,…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…The studies reported hematologic malignancy (10 studies), [27][28][29][30]34,41,43,45,48,54 solid malignancy (four studies), 31,44,47,50 or a combination of both (15 studies). 26,32,33,[35][36][37][38][39][40]42,46,49,[51][52][53] The studies also included rituximab-containing (seven studies), 27,28,30,34,41,43,54 non-rituximab (four studies), 31,42,44,46 or both regimens (seven studies), 32,33,36,38,40,48,49 and the remaining 11 studies did not specify chemotherapy types. 26,29,34,…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…2 There is evidence that chemotherapy can cause HBVr in patients with hematological malignancies. 3,4 HBVr can also occur in patients with rheumatic diseases undergoing immunosuppressive treatment. It is worth noting that biologics such as abatacept or rituximab can increase the risk of hepatitis B surface antigen (HBsAg) reverse seroconversion (RS) in rheumatoid arthritis (RA) patients with resolved hepatitis B.…”
Section: Introductionmentioning
confidence: 99%